Frequency coordination method of land mobile service in 150 MHz and 400 MHz bands in border areas - Hong REN; Yao BAO (Dianxin kexue)
The frequency planning for 150 MHz and 400 MHz bands of land mobile services in China and its neighboring countries was analyzed, and the status of related frequency assignments registered in ITU was studied. By comparing the existing frequency coordination methods, and the feasibility of channel allocations was analyzed, the coordination solutions for these bands were proposed.